Productivity and profitability of taro (Colocasia esculenta (L.) Schott) under drip and furrow irrigation - S. Sunitha; J. Suresh Kumar (JOURNAL OF ROOT CROPS, 2023)
Productivity and profitability of taro under drip irrigation and furrow irrigation was worked out based on the data collected from field experiments carried out at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala, India, for three years (2016-17 to 2018-19). The experiment was conducted in RBD, with upland taro variety, Muktakeshi, during summer, with seven treatments which included five levels of drip irrigation, furrow irrigation and a rainfed crop and three replications. The mean data over a period of three years indicated that drip irrigation @ 100% CPE resulted in the highest cormel yield, gross and net income and B:C ratio in taro. In addition to saving of irrigation water (30%), drip irrigation resulted in 45% increase in cormel yield, 57% increase in net income and 20% increase in B:C ratio, compared to furrow irrigation.